Effect of Water Hyacinth Bokashi and Stale Rice MOL Application on Growth and Yield of Cucumber - Rila Rahma Apriani; Anggres Tri Cahyaning; Antar Sofyan; Nur Laras Fitriyani; Bayu Kurniawan (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Cucumber (Cucumis sativus L.) is a vegetable plant from the Cucurbitaceae family whose production in Indonesia has decreased. Water hyacinth can be used as an organic fertilizer, and the application of Local Microorganisms (MOL) has been shown to improve the physical, chemical, and biological properties of the soil. This study aims to determine the effect of water hyacinth bokashi application and stale rice MOL on the growth and yield of cucumber plants and the most effective dose. Methodology: A factorial completely randomized design (CRD) was employed, utilizing 12 treatment combinations, which were repeated three times, resulting in 36 experimental units. The first factor is the Stale Rice MOL Factor (M), consisting of three levels, namely (M0) Control (M1) 100 ml/liter of water, (M2) 150 ml/liter of water. The second factor is Water Hyacinth. th Bokashi (E) with three levels, namely (E0) Control, (E1) 80 g / polybag, (E2) 130 g / polybag, (E3) 180 g / polybag. Findings: The findings indicated that the implementation of water hyacinth bokashi in conjunction with stale rice MOL exerted an influence on plant height parameters at 30 DAP. The optimal dosage of water hyacinth bokashi was determined to be 180 g/polybag in combination with stale rice MOL, equivalent to 150 ml/liter of water. Contribution: These results suggest that the integration of organic matter and local microbial inputs can serve as a sustainable alternative to synthetic fertilizers in cucumber cultivation, contributing to improved soil health and supporting environmentally friendly agricultural practices.